Fuel prices and commuting frequencies: Exploring revealed and anticipated changes among university students - Muhammad Abdullah; Nazam Ali; Muhammad Ashraf Javid; Muhammad Aamir Basheer (Journal of Urban Mobility)
The recent surge in fuel prices has disrupted daily life globally, with transportation costs posing a significant barrier to educational access and student retention. Rising fuel expenses may lead to reduced commuting frequency among students, particularly affecting those from disadvantaged socio-economic backgrounds. This study investigates the effects of rising fuel prices on university students’ commuting frequency across three phases: a pre-hike phase (late 2021), a current hike phase (early 2023), and a projected future hike phase (beyond mid-2023). Data were collected via a questionnaire survey from four private universities in Lahore, Pakistan. Revealed (actual) commuting frequency changes, based on differences between the pre-hike and current hike phases, and stated (anticipated) commuting frequency changes, based on stated intentions for the future hike phase, were analyzed. Trip frequency differences within and across fuel price phases were examined using bivariate hypothesis testing, while multinomial logistic regression was employed to identify significant predictors of across-phase trip frequency changes, controlling for the influence of socio-economic and demographic variables. Hypothesis testing showed significant differences in commuting behavior across phases, with a stronger intention to reduce trips during the future hike phase. Female students and private vehicle owners reported a significantly higher intention to reduce trips under the future fuel price scenario, and low-income students were also disproportionately affected. Multinomial logistic regression revealed that gender and commuting distance were significantly associated with anticipated changes. Female students were significantly less likely than males to indicate an intention to increase trips (relative to no change), suggesting that male students were more likely to expect increased commuting under the future hike scenario. Additionally, students commuting 5–10 km were nearly three times more likely than those commuting over 10 km to anticipate reducing their trips. These findings highlight unequal impacts of fuel price increases on student mobility and support the need for targeted transportation policies to ensure equitable access to higher education.